Use of Streptococcus Salivarius K12 in a cohort of PFAPA patients - Spagnolo, Alessandra; Mileto, Vincenzo; Civino, Adele; Maggio, Maria Cristina; Risso, Paolo; Sestito, Simona; Gallizzi, Romina (Frontiers in Pediatrics, 2024)
Periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis syndrome (PFAPA) is the most common cause of periodic fever in childhood.Although PFAPA is generally a self-limited condition, it can have negative impact on child's and parents' quality of life and family functioning.Our primary aim was to assess the potential effectiveness of Streptococcus Salivarius K12 (SSK12) in preventing febrile flares in PFAPA patients.Secondary aims were to evaluate the efficacy of SSK12 in reducing the severity of febrile attacks seen as a statistically significant reduction in the episode duration, highest fever temperature reached during fever, in the frequency of each associated symptom, calculated in the six months before and after the start of therapy.We valued 117 patients diagnosed with PFAPA based on Marshall's criteria, modified by Thomas et al and according to Eurofever/PRINTO classification criteria, aged 6 months to 9 years, with a median age at disease onset of 2years treated with SSK12 since January 2021 to January 2023. Data were collected both retrospectively and prospectively. Before using SS K12, febrile episodes recurred on average every 26.1 ± 11.5 days, with a febrile episode duration of 4.1 ± 1.4 days. The highest fever temperature during the episode was 39.8 ± 0.7 °C. After six months of SS K12, febrile episodes recurred on average every 70 ± 53,1 days (p value <0.01), the mean duration of febrile episodes was 3.3 ± 1.6 (p value <0.01) and the highest fever temperature reached during the febrile episode was 39.1 ± 1.1 °C (p value <0.01).We also documented a reduction in the frequency of exudative pharyngotonsillitis present in 72 vs 103 patients (p value <0.01), of oral aphthosis present in 47 vs 80 patients (p value <0.01), lateral cervical lymphadenopathy in 45 vs 83 (p value <0.01).Erythematous pharyngotonsillitis decreased in frequency but it was not statistically significant.Our results suggest that, the use of SS K12 could be beneficial in reducing febrile episodes related to PFAPA syndrome and its associated symptoms. It would be able to improve the quality of life in pediatric patients and the necessity of additional pharmacological therapies.